Growth, Yield, and Fiber Morphology of Kenaf (Hibiscus Cannabinus L.) Varieties Influenced by Different Levels of Npk Fertilizers - Rabar Fatah Salih (Journal of Applied Agricultural Science and Technology, 2022)
Different levels of NPK fertilizer were used to improve the growth, yield, and fiber morphology of two kenaf varieties. Therefore, a field experiment was conducted in the summer season of 2021 at the Grdarasha Field, College of Agricultural Engineering Sciences, Salahaddin University-Erbil. The results revealed that adding NPK at the rate of 100 kg/ha caused improved growth and yield characteristics includes; plant height, stem diameter, leaf number, and total fresh stem yield by almost (3.35 m, 25.88 mm, 250.10, and 246.93 t/ha), respectively. While, the best values of fresh and dry matter of core and bast fibers were recorded when NPK was applied at the proportion of 150 kg/ha which were (98.40, 57.80, 39.73, and 15.13 t/ha), respectively. Morphological properties of the kenaf bast fiber were also improved by adding NPK fertilizer. Both levels of NPK 100 and 150 kg/ha were noted to be the best for enhancing kenaf bast fiber compared to the control treatment. Finally, based on the results could recommend the farmers to use NPK fertilizer as a factor to increase fiber yield and improve its quality.